“Trained Immunity” from Mycobacterium spp. exposure (BCG vaccination and environmental) may have an impact on the incidence of early childhood leukemia - Singh, Samer; Kishore, Dhiraj; Singh, Rakesh K. (Frontiers in Immunology, 2023)
Preventive variables for childhood leukemia incidence (LI) remain unknown. Past assertions that childhood vaccinations, especially BCG, may be potentially protective have remained disputed for over five decades because of the lack of a unifying framework to explain variable outcomes in different studies. An examination of the early childhood LI for 2020 in European Region countries with supposedly similar underlying confounders but differential childhood vaccination coverage displays negative covariation with prevailing Mycobacterium spp. exposure in BCG-vaccinated children. The childhood LI in 0–4-year-old populations with >90% childhood BCG vaccination coverage is found to be strongly but negatively correlated with prevailing tuberculin immunoreactivity [r(24): -0.7868, p-value: < 0.0001]. No such correlation existed for the LI in 0–4-year-old populations without BCG vaccinations, though weak associations are hinted at by the available data for MCV2, PCV3, and DTP3 vaccinations. We hypothesize that early childhood BCG vaccination “priming” and subsequent “trained immunity” augmentation by “natural” boosting from Mycobacterium spp. exposure play a preventive and protective role in childhood LI. The non-consideration of prevailing “trained immunity” could have been a cause behind the conflicting outcomes in past studies. Exploratory studies, preferably performed in high-burden countries and controlling for the trained-immunity correlate and other potential confounders, would be warranted in order to establish a role for BCG vaccination and early-life immune training (or lack thereof) in childhood LI and help put the current controversy to rest.